'Meals on the mile: an ethnographic study of entrepreneurship and ethnic relations in Manchester's Curry Mile' - Davis, LC (2016)
Through a combination of international migration and the continuing growth of long-settled minority populations, British cities are more ethnically diverse than ever before. This diversity has led to the evolution of ethnic foodscapes, such as London’s ‘Brick Lane’ and Birmingham’s ‘Balti Quarter’. Using the case of Manchester’s ‘Curry Mile’ this thesis draws on evidence from interviews and participant observation to investigate entrepreneurship and ethnic relations. Firstly, it investigates why South Asian entrepreneurs open restaurants on the Mile. In doing so, it contributes empirical research to the push-pull theory of entrepreneurship, and finds that ‘pull’ factors generally retain greater influence than ‘push’ factors. Secondly, this thesis explores ethnic relations on the ‘Curry Mile’ and discovers that the Mile is paradoxically a site of ethnic conflict and cohesion. Overall, this thesis presents a long overdue ethnography of the Curry Mile, which is a vibrant ethnic foodscape that is often neglected by researchers.